Analyzing the Impact of Organizational Culture on Performance: A Study of Public and Private Hospitals in India - Paraminta Nambiyar (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This study aimed to analyze the impact of organizational culture on performance in public and private hospitals in India. A mixed-methods research design was used, involving a survey of hospital employees and interviews with hospital managers. The Organizational Culture Assessment Instrument (OCAI) was used to measure the four types of organizational cultures: clan, adhocracy, market, and hierarchy. Performance was measured using a composite score of patient satisfaction, clinical outcomes, financial performance, and employee satisfaction. The results showed that hierarchical culture was predominant in both types of hospitals, followed by clan, market, and adhocracy cultures. Private hospitals outperformed public hospitals in terms of overall hospital performance and employee satisfaction with the organizational culture. The findings suggest that healthcare managers and policymakers in India need to adopt more flexible and collaborative approaches to management, address the systemic issues facing public hospitals, and improve the work environment and employee engagement in public hospitals. Further research is needed to explore the relationship between organizational culture and other outcomes, such as patient satisfaction and clinical outcomes. The study adds to the growing body of literature on organizational culture in healthcare and provides valuable insights for healthcare managers and policymakers in India.